An Investigation of the Mosque Doors and Interior Window Shutters of Mimar Sinan in Istanbul in Terms of Materials, Dimension, Ornament, and Construction - Sogutlu, Cevdet; Dongel, Nihat; Togay, Abdullah; Dongel, Imran (Gazi Univ, 2014)
In this study, the investigation of wooden doors and interior window shutters which is present in mosques made by Mimar Sinan in Istanbul and bearing characteristic features of Ottoman period, are aimed to cover in terms of material, dimension, ornament, and construction. With the aid of the form of inventory which is developed in accordance with this aim, by identifying features of 13 mosques' main entrance doors and interior window shutters, which are made between the years of 1543-1589 in Istanbul were investigated. According to the results of the research, it is defined that walnut is used as a wooden material, all of the internal door and window shatters are symmetrical two-winged and composed of three clipboard and build in the authentic kundekari technique - while entrance doors of upper clipboards are decorated with a variety of motifs and calligraphy, windows shutters are left plain. In the middle and lower panels richly carved and inlaid decorations are used. In the implement of inlaid, as well as the materials like pearl and ivory, different types of wooden materials are used; in ornamentation, while ten-legged stars are preferred, also square matting, rectangle, octagon and hexagram motifs took place.
Keywords: Ottoman Art; Mimar Sinan; Wooden Doors; Ornament; Mosque Doors